A educação das relações étnico-raciais no currículo de uma escola quilombola no município de Guaçuí-ES. - Nogueira, Liliane Rosa (2020)
This study aimed to analyze the process of implementing Law No. 10,639 / 03 in the curriculum of the Municipal Elementary School José Antônio de Carvalho , which serves students from the Quilombola Córrego do Sossego Community, located in the District of